Aplikasi Sistem Informasi Pengajuan Cuti Karyawan Berbasis Web Pada PT. Gomeds Network - Ubaidillah Ubaidillah; Fatmawati Fatmawati (JTIM : Jurnal Teknologi Informasi dan Multimedia, 2021)
PT. Gomeds Network is an Internet Service Provider (ISP) company based in the city of Gorontalo. This company has problems or obstacles in the process of applying for leave for its employees where leave applications are still handled manually, even though personal computers are available as a support facility for work activities. All of this allows errors or inaccuracies in employee leave data at PT. Gomeds Network. The purpose of this research is to build a web-based employee leave application information system which makes it easier for employees to apply for leave and get complete and detailed information related to leave, also this leave application can be done online anywhere that can be done. connected to the internet so there is no need to meet with the staffing department. The research method used is the waterfall system development model or systems development life system (SDLC) with unified modeling language (UML) where the tools used to describe the system model are in the form of activity diagrams, use case diagrams, component diagrams and deployment diagrams and in making bases. data using entity relationship diagrams (ERD). With this employee leave application information system application can help employees in filing leave and make it easier for companies to process and manage employee leave data and incoming data can be stored safely in the database and can improve the performance and time efficiency in activities in the staffing department..